Bismuth vanadate photoanode with high charge separation efficiency and preparation method and application thereof
Through rapid thermal annealing technology, the nucleation and growth of bismuth vanadate particles is regulated, and the high charge separation efficiency and high crystallinity of BiVO4 photoanode are achieved, which solves the problem of insufficient charge separation ability of BiVO4 photoanode in traditional methods and improves the performance of photolysis aquatic oxygen reaction.
Patent Information
- Application Number
- CN202311115459.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-08-31
AI Technical Summary
The existing BiVO4 photoanode has low electron mobility and short hole diffusion distance, resulting in poor charge separation ability and low efficiency. It is difficult for traditional high-temperature treatment methods to obtain BiVO4 with high crystallinity and small particle size at the same time during the heat treatment process.
The rapid thermal annealing process is adopted to achieve rapid crystallization and nucleation growth of bismuth vanadate particles through ultra-high temperature increase rate and temperature, and the matching of particle size and hole diffusion distance is regulated to form a bismuth vanadate photoanode with high charge separation efficiency.
The charge separation efficiency and crystallinity of the bismuth vanadate photoanode has been significantly improved, and the trade-off between traditional methods is solved between high crystallinity and small particle size is improved, and the performance of photolysis aquatic oxygen reaction is improved.
Smart Images

Figure CN119530859A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photolysis of water to produce hydrogen, and specifically relates to a bismuth vanadate photoanode with high charge separation efficiency, a preparation method thereof, and an application thereof in a photolysis of water to produce oxygen reaction. Background Art
[0002] With the increasing severity of environmental pollution and the intensifying energy crisis in the world, it is imperative to find clean renewable energy to replace traditional fossil energy and achieve energy structure transformation. Photocatalytic water splitting hydrogen production technology can directly convert solar energy into green hydrogen energy, providing an effective means to accelerate the transformation of energy structure. Since the kinetic overpotential of the oxygen evolution reaction (OER) is as high as 0.25V, it is a bottleneck limiting the photocatalytic water splitting process. At present, a variety of semiconductor materials have been developed as photoanodes for OER, such as TiO 2 , WO 3 , Fe 2 O 3 、BiVO 4 , Si, etc. Among them, BiVO 4 It is the most popular photoanode material at present because of its suitable conduction band edge position, relatively wide band gap (2.4eV), good chemical stability, and low cost. 4 The electron mobility is low (0.02-0.044cm 2 V -1 s -1 ) and the short hole diffusion distance (~70nm), resulting in poor charge separation ability and serious photogenerated charge recombination, thus low efficiency.
[0003] In the past few decades, many strategies have been studied to improve BiVO. 4 The charge separation properties of BiVO2 can be improved by several strategies, including nanostructure synthesis, external / internal defect doping, heterojunction formation, surface passivation, and substrate modification. Almost all of these strategies require high temperature treatment (>400°C) to ensure the acquisition of highly active monoclinic scheelite BiVO2. 4 In addition, high temperature treatment promotes the decomposition of reactants to form BiVO with high crystallinity and low defect density. 4 As the heat treatment temperature increases, BiVO 4 The crystallinity of BiVO gradually increases, which has a positive effect on charge separation. 4 The particles gradually grew larger and even exceeded their hole diffusion length, which had an adverse effect on charge separation. By synthesizing BiVO with high crystallinity at ultra-high temperature (800°C), 4 Large particles, and then using ball milling to reduce the particle size, can effectively improve BiVO 4However, how to directly obtain BiVO with high crystallinity while maintaining small particle size during heat treatment? 4 It is a challenge to reduce the defect state density, meet the hole diffusion distance, and improve the photogenerated charge separation efficiency. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art, provide a bismuth vanadate photoanode with high charge separation efficiency and a preparation method thereof, and improve the performance of the bismuth vanadate photoanode in the photolysis of water to produce oxygen reaction.
[0005] The purpose of the present invention is achieved through the following technical solutions.
[0006] A bismuth vanadate photoanode with high charge separation efficiency comprises FTO conductive glass, a bismuth vanadate (BiVO4) layer and a NiFe(OH)X layer, wherein the FTO conductive glass, the bismuth vanadate (BiVO4) layer and the NiFe(OH)X layer are arranged in sequence from bottom to top, wherein the bismuth vanadate (BiVO4) layer is composed of bismuth vanadate (BiVO4) particles, the particle size of the bismuth vanadate (BiVO4) particles is 180-540nm, preferably 250nm, and the crystallinity is judged by the relative intensity of the diffraction peak in the X-ray diffraction diagram, preferably the high peak intensity (i.e., high crystallinity).
[0007] The transmittance of FTO conductive glass is 80% and the resistivity is 14Ω / □.
[0008] A bismuth vanadate (BiVO4) layer is formed on the surface of the FTO conductive glass by a metal organic decomposition method. The thickness of the bismuth vanadate (BiVO4) layer is 200-300nm, preferably 200-250nm.
[0009] The preparation method of bismuth vanadate photoanode with high charge separation efficiency is carried out according to the following steps:
[0010] Step 1, pretreatment of FTO conductive glass: ultrasonically clean the FTO conductive glass for 20-40 minutes, blow dry with nitrogen, and treat the FTO conductive glass with ultraviolet ozone equipment at 50-60° C. for 10-20 minutes to obtain a hydrophilic FTO conductive glass;
[0011] Step 2, preparation of bismuth vanadate (BiVO4): spin-coat a precursor solution uniformly dispersed with bismuth nitrate and vanadium acetylacetonate on the hydrophilic FTO conductive glass prepared in step 1 preheated to 45-65°C, and bake it in air as the baking atmosphere. The baking process adopts a two-step heating method: the first step of the heating process is to heat the room temperature (20-25°C) to 180-320°C at a heating rate of 4-12°C / min and then treat it for 8-24min; the second step of the heating process is to heat the room temperature (20-25°C) to 180-320°C at a heating rate of 5-5 After heating from 180-320°C to 360-850°C at a heating rate of 5°C / s and post-treatment for 8s-35min, a FTO / BiVO4 photoelectrode is obtained, wherein in the precursor solution, bismuth nitrate is bismuth nitrate pentahydrate, the amount of bismuth nitrate pentahydrate is 0.2390-0.2480g, the amount of vanadium acetylacetonate is 0.1290-0.1360g, the solvent is dimethyl sulfoxide, the amount is 450-550μL, and the spin coating amount of the precursor solution is 60-80μL;
[0012] Step 3, preparation of NiFe(OH)x: soak the FTO / BiVO4 photoelectrode prepared in step 2 in a co-catalyst precursor solution for 5-10s, dry it at 50-60°C for 0.5-1h, soak it in a 1M potassium hydroxide aqueous solution for 5-10min, take it out, wash it with deionized water, and blow dry it with nitrogen to obtain a bismuth vanadate photoanode (FTO / BiVO4 / NiFe(OH)x) with high charge separation efficiency, wherein the co-catalyst precursor solution is an aqueous solution of 25-35mM sodium citrate, 3-8mM ferric nitrate and 3-8mM nickel nitrate, and the amount of the precursor solution is 15-25μL.
[0013] In step 1, acetone, ethanol, and deionized water are used to ultrasonically clean the FTO conductive glass for 30 minutes to remove organic matter and other pollutants on its surface.
[0014] In step 2, the amount of bismuth nitrate pentahydrate used is 0.2425 g, the amount of vanadium acetylacetonate used is 0.1325 g, the amount of dimethyl sulfoxide used is 500 μL, and the amount of the precursor solution used is 75 μL.
[0015] In step 2, a spin coater is used to spin coat the precursor solution on the hydrophilic FTO conductive glass prepared in step 1 which is preheated to 50-60°C. The spin coating is divided into two stages, wherein the spin coating speed of the first stage is 1000-1200 r / min, and the duration is 20-30 s, and the spin coating speed of the second stage is 1500, 2500 or 3000 r / min, and the duration is 40 s.
[0016] In step 2, in the two-step heating method, the first heating process is to heat the temperature from room temperature (20-25°C) to 200-300°C at a heating rate of 5-10°C / min and then treat for 10-20 minutes; the second heating process is to heat the temperature from 200-300°C to 400-800°C at a heating rate of 6-50°C / s and then treat for 10s-30min.
[0017] In step 3, the co-catalyst precursor solution is an aqueous solution of 30 mM sodium citrate, 5 mM ferric nitrate and 5 mM nickel nitrate, and the amount of the precursor solution used is 20 μL.
[0018] The invention relates to the application of a bismuth vanadate photoanode with high charge separation efficiency in the photolysis of water to produce oxygen reaction, especially using the above bismuth vanadate photoanode as the anode of the photolysis of water reaction.
[0019] Under the conditions of 1M potassium borate buffer solution and AM 1.5G (i.e., irradiance of 100mW / c㎡) illumination, the bismuth vanadate photoanode can efficiently carry out water decomposition and oxygen production reaction. Relative to the reversible hydrogen electrode potential, the charge separation efficiency and charge injection efficiency at 1.23V are 82% and 85%, respectively, and the stability at 0.6V exceeds 300h.
[0020] The beneficial effects of the present invention are as follows: the present invention utilizes an ultra-high heating rate in a rapid thermal annealing process to achieve effective regulation of the nucleation growth process of bismuth vanadate, so that the particle size of bismuth vanadate matches its hole diffusion distance, thereby improving the efficiency of photogenerated charge separation. Compared with the traditional tubular furnace heat treatment process, the rapid thermal annealing used in the present invention can achieve a significant increase in the heating rate, thereby promoting the formation of bismuth vanadate particles.
[0021] The present invention utilizes the ultra-high temperature of the rapid thermal annealing process to achieve rapid crystallization of bismuth vanadate particles, reduce photogenerated charge recombination, and improve the efficiency of photogenerated charge separation. Compared with the traditional tubular furnace heat treatment process, the rapid thermal annealing used in the present invention can achieve a significant increase in the heat treatment temperature, greatly improving the crystallinity of bismuth vanadate;
[0022] The present invention utilizes the rapid thermal annealing heating rate and temperature regulation to improve the crystallinity of bismuth vanadate, while inhibiting the growth of bismuth vanadate particles, breaking through the long-standing trade-off between high crystallinity and small particle size in the bismuth vanadate photoanode heat-treated in a traditional tubular furnace;
[0023] The bismuth vanadate photoanode heat treatment process of the present invention has a low thermal budget, the preparation process has strong controllability and repeatability, and is economically feasible. At the same time, the bismuth vanadate photoelectrode of the present invention has excellent water decomposition performance and has certain industrial scale-up value. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1is a temperature-time diagram of the heat treatment process of Examples 1, 3, and 4 of the present invention;
[0025] Figure 2 The FTO / BiVO obtained in Examples 1, 3, and 4 of the present invention 4 Optical properties of the photoelectrode;
[0026] Figure 3 The FTO / BiVO obtained in Examples 1, 3, and 4 of the present invention 4 SEM photos of the photoelectrode and its particle size statistics;
[0027] Figure 4 The FTO / BiVO obtained in Examples 1, 3, 4, and 5 of the present invention 4 Grazing incidence X-ray diffraction pattern of the photoelectrode;
[0028] Figure 5 The FTO / BiVO obtained in Example 5 of the present invention 4 SEM image of the photoelectrode;
[0029] Figure 6 The FTO / BiVO obtained in Examples 1, 3, and 4 of the present invention 4 Sulfur oxidation photocurrent-voltage curve of the photoelectrode;
[0030] Figure 7 The FTO / BiVO obtained in Examples 1, 3, and 4 of the present invention 4 Graph of the charge separation efficiency of the photoelectrode;
[0031] Figure 8 The FTO / BiVO obtained in Example 2 of the present invention 4 / NiFe(OH) x Photocurrent-voltage curve of the photoelectrode;
[0032] Fig. 9 The FTO / BiVO obtained in Example 2 of the present invention 4 / NiFe(OH) x Water splitting stability curve of the photoelectrode;
[0033] Fig.10 The BiVO obtained in Examples 1, 3, and 4 of the present invention 4 Schematic diagram of bulk charge separation. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below through specific embodiments.
[0035] Example 1
[0036] (1) Pretreatment of FTO conductive glass
[0037] FTO conductive glass area is 2×2cm 2 The FTO conductive glass was ultrasonically cleaned with acetone, ethanol and deionized water for 30 minutes, and dried with nitrogen. It was treated with UV ozone equipment at 60°C for 15 minutes to obtain a hydrophilic FTO conductive glass.
[0038] (2) BiVO 4 Preparation
[0039] 0.2425g of bismuth nitrate pentahydrate and 0.1325g of vanadium acetylacetonate were mixed in 500μL of dimethyl sulfoxide and ultrasonicated at room temperature for 30min to obtain a 1M precursor solution. 75μL of the precursor solution was spin-coated on the FTO conductive glass preheated to 60°C using a spin coater. The first stage speed of the spin coating was 1000r / min for 20s, and the second stage speed was 2500r / min for 40s. After the spin coating, the sample was placed in a rapid thermal annealing furnace, with air as the baking atmosphere, and the temperature was increased from room temperature to 200°C at a rate of 10°C / min and maintained for 10min, and then the temperature was increased from 200°C to 800°C at a rate of 50°C / s for annealing for 20s to obtain FTO / BiVO 4 Photoelectrode.
[0040] Example 2
[0041] (1) Pretreatment of FTO conductive glass
[0042] FTO conductive glass area is 2×2cm 2 The FTO conductive glass was ultrasonically cleaned with acetone, ethanol and deionized water for 30 minutes, and dried with nitrogen. It was treated with UV ozone equipment at 60°C for 15 minutes to obtain a hydrophilic FTO conductive glass.
[0043] (2) BiVO 4 Preparation
[0044] 0.2425g of bismuth nitrate pentahydrate and 0.1325g of vanadium acetylacetonate were mixed in 500μL of dimethyl sulfoxide and ultrasonicated at room temperature for 30min to obtain a 1M precursor solution. 75μL of the precursor solution was spin-coated on the FTO conductive glass preheated to 60°C using a spin coater. The first stage speed of the spin coating was 1000r / min for 20s, and the second stage speed was 2500r / min for 40s. After the spin coating, the sample was placed in a rapid thermal annealing furnace, with air as the baking atmosphere, and the temperature was increased from room temperature to 200°C at a rate of 10°C / min and maintained for 10min, and then the temperature was increased from 200°C to 800°C at a rate of 50°C / s for annealing for 20s to obtain FTO / BiVO 4Photoelectrode.
[0045] (3)NiFe(OH) x Deposition of - References M.Li, T.Liu, Y.Yang, W.Qiu, C.Liang, Y.TongandY.Li, ACS Energy Lett., 2019, 4, 1983-1990
[0046] FTO / BiVO 4 The photoelectrode was immersed in 20 μL of precursor solution containing 30 mM sodium citrate, 5 mM ferric nitrate, and 5 mM nickel nitrate for 5 s and dried at 60 °C for 1 h. The obtained electrode was immersed in 1 M KOH for 5 min to convert the complex into hydroxide, and then rinsed with deionized water and washed with N 2 Drying to remove excess hydroxide to form NiFe(OH) x catalyst.
[0047] Example 3
[0048] (1) Pretreatment of FTO conductive glass
[0049] FTO conductive glass area is 2×2cm 2 The FTO conductive glass was ultrasonically cleaned with acetone, ethanol and deionized water for 30 minutes, and dried with nitrogen. It was treated with UV ozone equipment at 60°C for 15 minutes to obtain a hydrophilic FTO conductive glass.
[0050] (2) BiVO 4 Preparation
[0051] 0.2425g of bismuth nitrate pentahydrate and 0.1325g of vanadium acetylacetonate were mixed in 500μL of dimethyl sulfoxide and ultrasonicated at room temperature for 30min to obtain a 1M precursor solution. 75μL of the precursor solution was spin-coated on FTO conductive glass preheated to 60°C using a spin coater. The first stage speed of the spin coating was 1000r / min for 20s, and the second stage speed was 2500r / min for 40s. After the spin coating was completed, the sample was placed in a traditional tube furnace, with air as the baking atmosphere, and the temperature was raised from room temperature to 500°C at a heating rate of 5°C / min for 1h, and then cooled naturally.
[0052] Example 4
[0053] (1) Pretreatment of FTO conductive glass
[0054] FTO conductive glass area is 2×2cm 2The FTO conductive glass was ultrasonically cleaned with acetone, ethanol and deionized water for 30 minutes, and dried with nitrogen. It was treated with UV ozone equipment at 60°C for 15 minutes to obtain a hydrophilic FTO conductive glass.
[0055] (2) BiVO 4 Preparation
[0056] 0.2425g of bismuth nitrate pentahydrate and 0.1325g of vanadium acetylacetonate were mixed in 500μL of dimethyl sulfoxide and ultrasonicated at room temperature for 30min to obtain a 1M precursor solution. 75μL of the precursor solution was spin-coated on FTO conductive glass preheated to 60°C using a spin coater. The first stage speed of the spin coating was 1000r / min for 20s, and the second stage speed was 2500r / min for 40s. After the spin coating was completed, the sample was placed in a traditional tube furnace, with air as the baking atmosphere, and the temperature was raised from room temperature to 500°C at a heating rate of 5°C / min for 2h, and then cooled naturally.
[0057] Example 5
[0058] (1) Pretreatment of FTO conductive glass
[0059] FTO conductive glass area is 2×2cm 2 The FTO conductive glass was ultrasonically cleaned with acetone, ethanol and deionized water for 30 minutes, and dried with nitrogen. It was treated with UV ozone equipment at 60°C for 15 minutes to obtain a hydrophilic FTO conductive glass.
[0060] (2) BiVO 4 Preparation
[0061] 0.2425g of bismuth nitrate pentahydrate and 0.1325g of vanadium acetylacetonate were mixed in 500μL of dimethyl sulfoxide and ultrasonicated at room temperature for 30min to obtain a 1M precursor solution. 75μL of the precursor solution was spin-coated on FTO conductive glass preheated to 60°C using a spin coater. The first stage speed of the spin coating was 1000r / min for 20s, and the second stage speed was 2500r / min for 40s. After the spin coating, the sample was placed in a rapid thermal annealing furnace, with air as the baking atmosphere, and the temperature was increased from room temperature to 200°C at a heating rate of 10°C / min and maintained for 10min, and then the temperature was increased from 200°C to 800°C at a heating rate of 12, 25, and 50°C / s for annealing for 20s.
[0062] As attached Figure 4 As shown, the FTO / BiVO obtained in Example 5 4 Grazing incidence X-ray diffraction pattern of the photoelectrode. The higher the heating rate, the sharper the X-ray diffraction peak and the higher the crystallinity.
[0063] like Figure 5 As shown, the FTO / BiVO obtained in Example 5 4 Scanning electron microscope image of the photoelectrode. All samples show a nanoporous structure. The higher the heating rate, the smaller the particle size and the greater the number of particles. Therefore, the optimized rate is 50℃ / s.
[0064] like Figure 1 As shown, compared with the traditional furnace tube heating process of Examples 3 and 4, the rapid thermal annealing process of Example 1 is used to heat treat bismuth vanadate, which can shorten the heat treatment time by 80% and reduce the thermal budget.
[0065] like Figure 2 As shown, the FTO / BiVO obtained in Examples 1, 3, and 4 4 The transmittance, reflectivity, absorptivity and absorption spectrum of the photoelectrode relative to the solar spectrum show that the BiVO 4 The light absorption rates are almost the same, indicating that the charge production efficiency is the same.
[0066] like Figure 3 As shown, the FTO / BiVO obtained in Examples 1, 3, and 4 4 Scanning electron microscope photos of the photoelectrode and the statistics of its particle size. All samples showed nanoporous structures. The BiVO obtained in Examples 1, 3, and 4 4 The average particle sizes are 256, 258, and 402 nm respectively.
[0067] like Figure 4 As shown, the FTO / BiVO obtained in Examples 1, 3, and 4 4 Grazing incidence X-ray diffraction patterns of the photoelectrodes. X-ray diffraction peak sharpness: Example 1 > Example 4 > Example 3, crystallinity: Example 1 > Example 4 > Example 3.
[0068] like Figure 6 As shown, the FTO / BiVO obtained in Examples 1, 3, and 4 4 The sulfur oxidation photocurrent-voltage curve of the photoelectrode. Compared with the bismuth vanadate photoanode treated by tube furnace in Example 3 and Example 4, the FTO / BiVO photoanode treated by rapid thermal annealing in Example 1 4 Photoanodes can enhance the photoelectrochemical performance.
[0069] like Figure 7 As shown, the FTO / BiVO obtained in Examples 1, 3, and 4 4 Figure 2 shows the charge separation efficiency of the photoelectrode. Compared with the bismuth vanadate photoanode treated in a tube furnace in Example 3 and Example 4, the FTO / BiVO photoanode treated in a rapid thermal annealing process in Example 1 4Photoanode can effectively improve the charge separation efficiency.
[0070] like Figure 8 As shown, FTO / BiVO 4 / NiFe(OH) x Photocurrent-voltage curve of the photoelectrode, rapid annealing treatment of BiVO 4 The heating rate of the process is 50℃ / s, the thermal annealing temperature is 800℃, and the time is 20s. The water oxidation performance shows that FTO / BiVO 4 / NiFe(OH) x The starting potential of the photoelectrode is 0.25 V (vs. RHE), and the photocurrent density at 1.23 V (vs. RHE) is about 2.7 mA / cm 2 , the charge injection efficiency is as high as 85%.
[0071] Fig. 9 The FTO / BiVO obtained in Example 2 of the present invention 4 / NiFe(OH) x Water splitting stability curve of the photoelectrode.
[0072] The bismuth vanadate photoanode with high charge separation efficiency of the present invention is used in the photolysis of water process, and the prepared FTO / BiVO 4 / NiFe(OH) x The photoanode was used as the working electrode, the Pt sheet was used as the counter electrode, and the Hg / HgO electrode was used as the reference electrode. The photocatalytic water splitting activity test was carried out in 1MKBi electrolyte. Fig. 9 As shown, FTO / BiVO 4 / NiFe(OH) x Water oxidation stability curve of photoanode, rapid annealing treatment of BiVO 4 The heating rate of the process was 50°C / s, the thermal annealing temperature was 800°C, and the time was 20s. After 350 hours of water decomposition test, the current density of the photoelectrode only decreased by 20%, indicating that the photoanode has high stability.
[0073] like Fig.10 As shown, the BiVO obtained in Examples 1, 3, and 4 4 Schematic diagram of bulk charge separation. FTO / BiVO treated by rapid thermal annealing in Example 1 4 The photoanode can maintain a small particle size while avoiding the generation of defect states, effectively improving the charge separation efficiency. However, the charge recombination of the bismuth vanadate bulk phase in Example 3 and Example 4 using a tube furnace heat treatment is serious.
[0074] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a bismuth vanadate photoanode with high charge separation efficiency, characterized in that: Follow the steps below: Step 1, pretreatment of FTO conductive glass: ultrasonically clean the FTO conductive glass for 20-40 minutes, blow dry with nitrogen, and treat the FTO conductive glass with ultraviolet ozone equipment at 50-60° C. for 10-20 minutes to obtain a hydrophilic FTO conductive glass; Step 2, preparation of bismuth vanadate (BiVO4): spin-coat a precursor solution uniformly dispersed with bismuth nitrate and vanadium acetylacetonate on the hydrophilic FTO conductive glass prepared in step 1 preheated to 45-65°C, and bake it in air as the baking atmosphere. The baking process adopts a two-step heating method: the first step of the heating process is to heat the room temperature (20-25°C) to 180-320°C at a heating rate of 4-12°C / min and then treat it for 8-24min; the second step of the heating process is to heat the room temperature (20-25°C) to 180-320°C at a heating rate of 5-5 After heating from 180-320°C to 360-850°C at a heating rate of 5°C / s and post-treatment for 8s-35min, a FTO / BiVO4 photoelectrode is obtained, wherein in the precursor solution, bismuth nitrate is bismuth nitrate pentahydrate, the amount of bismuth nitrate pentahydrate is 0.2390-0.2480g, the amount of vanadium acetylacetonate is 0.1290-0.1360g, the solvent is dimethyl sulfoxide, the amount is 450-550μL, and the spin coating amount of the precursor solution is 60-80μL; Step 3, preparation of NiFe(OH)x: soak the FTO / BiVO4 photoelectrode prepared in step 2 in a co-catalyst precursor solution for 5-10s, dry it at 50-60°C for 0.5-1h, soak it in a 1M potassium hydroxide aqueous solution for 5-10min, take it out, wash it with deionized water, and blow dry it with nitrogen to obtain a bismuth vanadate photoanode (FTO / BiVO4 / NiFe(OH)x) with high charge separation efficiency, wherein the co-catalyst precursor solution is an aqueous solution of 25-35mM sodium citrate, 3-8mM ferric nitrate and 3-8mM nickel nitrate, and the amount of the precursor solution is 15-25μL.
2. The method for preparing a bismuth vanadate photoanode with high charge separation efficiency according to claim 1, characterized in that: In step 1, the FTO conductive glass is ultrasonically cleaned with acetone, ethanol, and deionized water for 30 minutes respectively.
3. The method for preparing a bismuth vanadate photoanode with high charge separation efficiency according to claim 1, characterized in that: In step 2, the amount of bismuth nitrate pentahydrate used is 0.2425 g, the amount of vanadium acetylacetonate used is 0.1325 g, the amount of dimethyl sulfoxide used is 500 μL, and the amount of the precursor solution used is 75 μL.
4. The method for preparing a bismuth vanadate photoanode with high charge separation efficiency according to claim 1, characterized in that: In step 2, a spin coater is used to spin coat the precursor solution on the hydrophilic FTO conductive glass prepared in step 1 which is preheated to 50-60°C. The spin coating is divided into two stages, wherein the spin coating speed of the first stage is 1000-1200 r / min, and the duration is 20-30 s, and the spin coating speed of the second stage is 1500, 2500 or 3000 r / min, and the duration is 40 s.
5. The method for preparing a bismuth vanadate photoanode with high charge separation efficiency according to claim 1, characterized in that: In step 2, in the two-step heating method, the first heating process is to heat the temperature from room temperature (20-25°C) to 200-300°C at a heating rate of 5-10°C / min and then treat for 10-20 minutes; the second heating process is to heat the temperature from 200-300°C to 400-800°C at a heating rate of 6-50°C / s and then treat for 10s-30min.
6. The method for preparing a bismuth vanadate photoanode with high charge separation efficiency according to claim 1, characterized in that: In step 3, the co-catalyst precursor solution is an aqueous solution of 30 mM sodium citrate, 5 mM ferric nitrate and 5 mM nickel nitrate, and the amount of the precursor solution used is 20 μL.
7. A bismuth vanadate photoanode with high charge separation efficiency prepared by the method according to any one of claims 1 to 6, characterized in that: It includes FTO conductive glass, bismuth vanadate (BiVO4) layer and NiFe(OH)X layer, which are arranged in sequence from bottom to top, wherein the bismuth vanadate (BiVO4) layer is composed of bismuth vanadate (BiVO4) particles, and the particle size of the bismuth vanadate (BiVO4) particles is 180-540nm, preferably 250nm.
8. The bismuth vanadate photoanode with high charge separation efficiency according to claim 7, characterized in that: The transmittance of FTO conductive glass is 80% and the resistivity is 14Ω / □.
9. The bismuth vanadate photoanode with high charge separation efficiency according to claim 7, characterized in that: The thickness of the bismuth vanadate (BiVO4) layer is 200-300 nm, preferably 200-250 nm.
10. Use of the bismuth vanadate photoanode with high charge separation efficiency as claimed in any one of claims 7 to 9 in a photolysis of water to produce oxygen reaction, in particular using the bismuth vanadate photoanode as the anode of the photolysis of water reaction, characterized in that: The bismuth vanadate photoanode with high charge separation efficiency can efficiently carry out water decomposition and oxygen production reaction under the conditions of 1M potassium borate buffer solution and AM 1.5G (i.e., irradiance of 100mW / c㎡). Relative to the reversible hydrogen electrode potential, the charge separation efficiency and charge injection efficiency at 1.23V are 82% and 85%, respectively, and the stability at 0.6V exceeds 300h.
Citation Information
Patent Citations
Bismuth vanadate photo-anode film and preparation method thereof
CN108408776A